Comparative study of thermostimulated luminescence and electron emission of nitrogen nanoclusters and films - Boltnev, R.E.; Bykhalo, I.B.; Krushinskaya, I.N.; Pelmenev, A.A.; Khmelenko, V.V.; Lee, D.M.; Khyzhniy, I.V.; Uyutnov, S.A.; Savchenko, E.V.; Ponomaryov, A.N.; Gumenchuk, G.B.; Bondybey, V.E. (Физика низких температур, 2013)
We have studied thermostimulated luminenscence and electron emission of nitrogen films and nanoclusters containing atomic nitrogen free radicals. Thermostimulated electron emission from N₂ nanoclusters was ob-served for the first time. Thermostimulated luminescence spectra obtained during N₂–He sample destruction are similar to those detected from N₂ films pre-irradiated by an electron beam. This similarity reveals common mechanisms of energy transfer and relaxation. The correlation of the luminescence intensity and the electron cur-rent in both systems points to the important role of ionic species in relaxation cascades. A sublimation of solid helium shells isolating nitrogen nanoclusters is a trigger for the initiation of thermostimulated luminescence and electron emission in these nitrogen–helium condensates.